2020
DOI: 10.21273/hortsci15414-20
|View full text |Cite
|
Sign up to set email alerts
|

Identities of and Phenotypic Variation for Epicuticular Waxes among Leaves and Plants from Inbred Onion Populations

Abstract: The amounts and types of epicuticular waxes on onion (Allium cepa) leaves affect feeding damage by onion thrips (Thrips tabaci). This study used gas chromatography mass spectrometry (GCMS) to establish the identities of waxes and measure over time wax amounts on leaves of inbred onion plants with glossy, semiglossy, and waxy foliage. Nine waxes were detected on leaves of all inbreds, and higher coefficients of variation (cv) were observed for less abundant waxes on foliage of doubled haploid onions. Older leav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Our results indicate that amounts of waxes on onion foliage should be measured under protected conditions to better reveal phenotypic variation. We previously reported that multiple sampling of leaves on the same plant over time and environments may not be necessary (Khosa et al, 2020), and resources may be better used to sample greater numbers of plants. Reducing the amount of H16 while maximizing amounts of fatty alcohols and/or alkanes may produce onion populations with semi-glossy foliage that accumulate enough total epicuticular wax to perform well in field production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results indicate that amounts of waxes on onion foliage should be measured under protected conditions to better reveal phenotypic variation. We previously reported that multiple sampling of leaves on the same plant over time and environments may not be necessary (Khosa et al, 2020), and resources may be better used to sample greater numbers of plants. Reducing the amount of H16 while maximizing amounts of fatty alcohols and/or alkanes may produce onion populations with semi-glossy foliage that accumulate enough total epicuticular wax to perform well in field production.…”
Section: Discussionmentioning
confidence: 99%
“…Data analysis. Post-run GCMS analyses (Shimadzu) were used to determine peak areas and identities of waxes as described by Khosa et al (2020). Peak areas were adjusted by dividing the peak areas for docosane and therefore represent peak areas per gram leaf fresh weight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To prepare for gas chromatographymass spectrometry (GCMS), dried wax extracts were dissolved in 250 mL chloroform, 300 mL acetronitrile (HPLC grade; Thermo Fisher Scientific), and 105 mL N,O bis(trimethylsilyl) trifluoro-acetamide (HPLC/GC grade; Sigma-Aldrich) and incubated for 30 min at 80°C. Identification and quantification of waxes involved the GCMS conditions described by Damon et al (2014) and Khosa et al (2020).…”
Section: Methodsmentioning
confidence: 99%